Parent Involvement and Student Achievement in the Gulf Cooperation Council Countries: Evidence from PIRLS 2016 Data - Shefa AlHashmi (Gulf Education and Social Policy Review)
Abstract Numerous studies have shown that parental involvement has a significant influence on student achievement. However, most of these studies have been conducted in Western Europe and North America. In the Gulf Cooperation Council (GCC) region, we find that quantitative research that examines parents' behavior is limited. In order to design efficient parent engagement programs and family policies, we need to understand how parents interact with their children's education in this area. Data from PIRLS is the only open-access data that allows us to study parent involvement by using a large sample that may reveal parents' behavior patterns. This work investigates elements of parental involvement addressed in the parent questionnaire of PIRLS and studies its relationship to student reading achievement. The results showed a positive influence of parents' practice of educational activities and expectations of their children's educational achievement, and a negative association between student reading achievement and parents' help with homework. Implications are discussed from the perspective of the social context in the GCC.